Pengembangan Sistem Penyiraman Tanaman Otomatis Berbasis Arduino dan Indeks Kenyamanan Untuk Vertical Garden di RT 03 RW 07 Kelurahan Sumber, Kecamatan Banjarsari, Kota Surakarta - Fadhil Achmad Zaky (ENVIRO: Journal of Tropical Environmental Research, 2026)
The decline of green spaces in urban areas due to land conversion has prompted the need for innovative solutions such as vertical gardens. However, maintenance faces obstacles, including limited access to water and community participation. This research aims to develop an IoT-based automatic watering system for vertical gardens in RT 03 RW 07 Sumber Village, Surakarta, by utilizing the ESP32 Dev Kit V4 microcontroller, DHT22 (temperature/humidity) sensor, and capacitive soil moisture sensor. The system is designed to automatically activate the water pump when soil moisture is <50%, monitored in real-time via 4G LTE module. Research methods include observation, interviews, experiments, and quantitative data analysis (descriptive statistics, comparative, and validity/reliability tests). The trial results showed that the system operated effectively with an average soil moisture of 73-74.6%, but implementation faced challenges such as instability of electricity/internet infrastructure (45% of respondents doubted its reliability) and economic participation fee preference (55% chose Rp25,000). Analysis of respondents' perceptions (N=20) revealed the need for technical education and strengthening of fail-safe features to increase adoption. This study concludes that IoT-based watering systems have potential as a sustainable solution for urban vertical gardens, with recommendations for supporting infrastructure optimization and affordable community participation models.